Diagnosis and treatment of cancer‐related anemia. Issue 2 (February 2014) - Gilreath, Jeffrey A.; Stenehjem, David D.; Rodgers, George M.
<x xml:space="preserve">Abstract</x> Cancer‐related anemia (CRA) is due to multiple etiologies, including chemotherapy‐induced myelosuppression, blood loss, functional iron deficiency, erythropoietin deficiency due to renal disease, marrow involvement with tumor as well as other factors. The most common treatment options for CRA include iron therapy, erythropoietic‐stimulating agents (ESAs), and red cell transfusion. Safety concerns as well as restrictions and reimbursement issues surrounding ESA therapy for CRA have resulted in suboptimal treatment. Similarly, many clinicians are not familiar or comfortable using intravenous iron products to treat functional iron deficiency associated with CRA. This article summarizes our approach to treating CRA and discusses commonly encountered clinical scenarios for which current clinical guidelines do not apply. Am. J. Hematol. 89:203–212, 2014. © 2013 Wiley Periodicals, Inc.